CFD Simulation of Electrostatic Charging in Gas-Solid Fluidized Beds: Model Development Through Fundamental Charge Transfer Experiments - Chowdhury, Fahad Al-Amin (Université d'Ottawa / University of Ottawa, 2021)
The triboelectrification of particles by contact or frictional charging is known to be an operational challenge in the polyolefin industry. Particularly in polyethylene production, gas-solid fluidized bed reactors are known to be susceptible to electrostatic charging due to the rigorous mixing of polyethylene and catalyst particles in a dry environment. The presence of charged particles coupled with a highly exothermic polymerization reaction results in sheet formation on the reactor walls. This behaviour can decrease reactor performance and obstruct the system, consequently forcing a shutdown for reactor maintenance. The generation of electrostatic charge in fluidized beds has been widely studied throughout the years; however, limited attention has been paid to the simulation and modeling of this phenomenon. Since it is difficult to accurately quantify the charge generation in industrial fluidized beds, developing an electrostatic model based on material properties would considerably aid in providing insight on this occurrence and its effects. A computational fluid dynamics (CFD) model that incorporates this electrostatic model can then be used as a predictive tool in research and development. Simulating electrostatic charging in gas-solid fluidized beds would be a cost-effective alternative to running experiments on them, especially for industrial-scale test runs. In this thesis, an electrostatic charging model was developed to be used in conjunction with an Euler-Euler Two-Fluid CFD model to simulate triboelectrification and its effects in gas-solid flows. The electrostatic model was first established for mono-dispersed gas-particle flows and was validated using past experimental findings of particle charging for gas-solid fluidization runs. With the goal of providing a realistic representation of gas-solid fluidization of polyethylene resins with a wide particle-size distribution, the electrostatic model was extended to consider bi-dispersed particulate flow systems. Simulation results using this model show the prediction of bipolar charging when the particles have different sizes, even though they are made of the same material. This phenomenon is analyzed and is shown to be driven by the electric field produced by the charge accumulated on the particles. Experimental studies of particle-wall and particle-particle contact charging were performed to investigate the electrostatic and mechanical parameters that are crucial for modeling the magnitude and direction of charge transfer in gas-solid flow systems. Particle-wall contact charging due to single and repeated collisions were tested with various particles, including commercial linear low-density polyethylene, to determine their rates of charging as well as their charge saturation limits when colliding with a metal surface. Plotting the charge saturation value of the particles against their respective surface areas revealed a linear trend which could be used to calculate the charge saturation of the particle for a given particle size. Additional particle-wall charging studies include the effect of initial charge, collision frequency, particle type, impact angle, impact velocity and the presence of impurities on particle charging. To study particle-particle contact charging, a novel apparatus was designed, built, and tested to determine the magnitude and direction of charge transfer due to the individual particle-particle collisions of insulator particles. This apparatus was the first of its kind, and it ensured that the measured charge transfer for each experimental trial was solely due to the binary collision between the particles. It was observed that the direction of charge transfer in identical particle collisions is not dictated by the net initial charges of the particles, but the localized charge difference at the particles’ contacting surface. Moreover, particle-particle collisions of nylon particles of varying sizes confirmed the bipolar charging phenomena, where the direction of charging was dictated by the relative size of the colliding particles. These findings, among others, contradict the charge transfer behavior predicted by electrostatic charging models currently proposed for particle-particle collisions. As such, it was concluded that an empirically accurate charge transfer model needs to be established to simulate the electrostatic charging of particles in poly-dispersed gas-solid flow systems.
Keywords: Electrostatics; Triboelectrification; Gas-Solid Fluidization; CFD Modeling